Respuesta :
3a + 6b = 12 and
-3a + 6b = -12
if we add the equations, the -3a cancels out leaving:
12b = 0
if we plug it into the first equation, we get 3a + 0 = 12, which simplifies the equation to:
3a = 12
Divide both sides by three and the result is:
a = 4
The final answer is:
a = 4
b = 0
-3a + 6b = -12
if we add the equations, the -3a cancels out leaving:
12b = 0
if we plug it into the first equation, we get 3a + 0 = 12, which simplifies the equation to:
3a = 12
Divide both sides by three and the result is:
a = 4
The final answer is:
a = 4
b = 0